The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 5th Annual International Conference on Accounting Research (AICAR 2018) 2019
DOI: 10.2991/aicar-18.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Profitability, Firm Size, and Earnings Management: the Moderating Effect of Managerial Ownership

Abstract: This research examines the effect of Profitability and firm size on earnings management with managerial ownership as moderation. The total sample in this research as many as 60 companies listed in Indonesia Stock Exchange in the period 2012-2016. Test results show that profitability has a positive effect on earnings management and firm size negatively affect earnings management. Managerial ownership is not a moderating variable profitability and firm size influence on earnings management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 1 publication
0
5
0
5
Order By: Relevance
“…Semakin besar ukuran perusahaan, maka semakin tinggi nilai atau kekayaan perusahaan yang dapat digunakan dalam mendukung aktivitas operasional usaha. Adanya pengaruh yang negatif diantara variabel ukuran perusahaan dan variabel manajemen laba sesuai dengan paparan dari Swastika (2013), Purnama & Nurdiniah (2019) dimana pendapat tersebut didukung oleh Hassan & Ahmed (2012) yang menyatakan bahwa semakin besar ukuran perusahaan, maka semakin kecil pula pengelolaan manajemen laba yang dilakukan di perusahaannya.…”
Section: Pengaruh Ukuran Perusahaan Terhadap Manajemen Labaunclassified
“…Semakin besar ukuran perusahaan, maka semakin tinggi nilai atau kekayaan perusahaan yang dapat digunakan dalam mendukung aktivitas operasional usaha. Adanya pengaruh yang negatif diantara variabel ukuran perusahaan dan variabel manajemen laba sesuai dengan paparan dari Swastika (2013), Purnama & Nurdiniah (2019) dimana pendapat tersebut didukung oleh Hassan & Ahmed (2012) yang menyatakan bahwa semakin besar ukuran perusahaan, maka semakin kecil pula pengelolaan manajemen laba yang dilakukan di perusahaannya.…”
Section: Pengaruh Ukuran Perusahaan Terhadap Manajemen Labaunclassified
“…Research from Purnama and Nurdiniah (2018) explained that profitability affect positively to earnings management. It also corresponds to the research done by Khanh and Khuong (2018); Fitri et al (2018); Zakia et al (2019);and Pasaribu et al (2019).…”
Section: Relationship Of Managerial Ownership and Institutional Ownership Towards Earnings Management With Profitability As Moderating Vamentioning
confidence: 99%
“…Previous studies indicated a significant relation which found that larger firms use accounting manipulation more than other firms. Larger firms generally have more complex internal control systems than small firms, which reduces the likelihood of earnings management (Purnama & Nurdiniah, 2019;Sharf & Abu-Nassar, 2021).…”
Section: Company Size (Logsiz)mentioning
confidence: 99%
“…The ratio of return on assets is usually used as proxy of accounting performance (Purnama & Nurdiniah, 2019). Alzoubi (2016) found that the quality of earnings management is lower in companies with higher ROA, and document a negative association between ROA and discretionary accruals, while Lopes (2018) found that discretionary accruals are significantly and positively correlated with firm performance.…”
Section: Company Profitability (Roa)mentioning
confidence: 99%